General purpose MDE tools - Palacios-González, Elías; Fernández-Fernández, Héctor; García-Díaz, Vicente; Pelayo García-Bustelo, B. Cristina; Cueva Lovelle, Juan Manuel; Sanjuán Martínez, Óscar (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
MDE paradigm promises to release developers from writing code. The basis of this paradigm consists in working at such a level of abstraction that will make it easyer for analysts to detail the project to be undertaken. Using the model described by analysts, software tools will do the rest of the task, generating software that will comply with customer's defined requirements. The purpose of this study is to compare general purpose tools available right now that enable to put in practice the principles of this paradigm and aimed at generating a wide variety of applications composed by interactive multimedia and artificial intelligence components.
Keywords: MDA; MDD; MDE; software factories; IJIMAI